The identity of the musical performer: marks and possibilities of declassification (PerCursos, 2021)
Musical performance appears as a very classified field - regarding Gutiérrez (2007) understanding of the term - and, as a consequence, also as a very colonized field, what reflects directly in the identity of the musical performer and in its musical practices. So, this paper aims to analyze the performer’s identity to stablish, from this comprehension, some possible escape routes towards more plural musical practices. The methodology of this work consists in the analysis of the performer’s identity in the light of Gutiérrez’s concepts of declassification, classification and identity (2007, 2009, 2020), in dialogue with the specific literature of the musical scope. The choice of this theoretical background is justified by its potential to open for the logical pluralism, that stablishes itself in opposition to the consensus and the hegemonic knowledge. Furthermore, this theoretical background has already been successfully applied in the field of jazz studies by Mendes (2016). From this proposition of analysis, observation and identification of the identity and territorial marks that configures the musical performer, we present two strategies of declassification: the oxymoron and the polysemy. This process of declassification is, most of all, an emancipating and decolonizing process, which has the purpose to create possibilities to non-hegemonic and plural musical practices, where absent artistic narratives may emerge. At last, the practical application of these strategies is exemplified through the description of an artistic research project in progress entitled “Aos olhos da areia”.
Keywords: musical performance; declassification; identity; artistic research